2019
DOI: 10.1002/per.2180
|View full text |Cite
|
Sign up to set email alerts
|

Does Cooperation in the Laboratory Reflect the Operation of A Broad Trait?

Abstract: The Dictator Game, a face valid measure of altruism, and the Trust Game, a face valid measure of trust and trustworthiness, are among the most widely used behavioural measures in human cooperation research. Researchers have observed considerable covariation among these and other economic games, leading them to assert that there exists a general human propensity to cooperate that varies in strength across individuals and manifests itself across a variety of social settings. To formalize this hypothesis, we crea… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
26
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 29 publications
(27 citation statements)
references
References 86 publications
(129 reference statements)
1
26
0
Order By: Relevance
“…Second, these studies usually only use one economic game, which may lower their generalizability [44]. In accordance with this idea, McAuliffe et al [45] found that single economic games do not correlate with real-life cooperation, but a general factor based on several economic games does. Finally, there is increasing evidence that economic games lack ecological validity [46].…”
Section: Introductionmentioning
confidence: 99%
“…Second, these studies usually only use one economic game, which may lower their generalizability [44]. In accordance with this idea, McAuliffe et al [45] found that single economic games do not correlate with real-life cooperation, but a general factor based on several economic games does. Finally, there is increasing evidence that economic games lack ecological validity [46].…”
Section: Introductionmentioning
confidence: 99%
“…A myriad of traits have been shown to be related to social dilemma choices including rather narrow constructs such as altruism (e.g., Haesevoets et al, 2018;McAuliffe et al, 2019), social value orientation (e.g., Balliet, Parks, & Joireman, 2009), and the dark triad (e.g., Bereczkei & Czibor, 2014;Campbell, Bush, Brunell, & Shelton, 2005;Mokros et al, 2008). The list also includes broader constructs such as agreeableness (e.g., Volk, Thöni, & Ruigrok, 2011) from the Big Five model (Goldberg, 1990) and honesty-humility (e.g., Hilbig, Zettler, & Heydasch, 2012) from the HEXACO model (Lee & Ashton, 2004).…”
Section: Individual Differences In Social Dilemma Choicesmentioning
confidence: 99%
“…Other papers focused on the structure of different aspects of personality (e.g. human values, Coelho, Hanel, Johansen, & Maio, ; cooperative behaviour in economic games, McAuliffe, Forster, Pedersen, & McCullough, ; and narcissism, Rogoza, Cieciuch, Strus, & Baran, ), self‐regulatory (e.g. Hennecke, Czikmantori, & Brandstätter, ), and biological (e.g.…”
mentioning
confidence: 99%